Strategi dan Gaya Pengambilan Keputusan Pemimpin HIMA dalam Penentuan Proker Unggulan Selingkup FISIPOL di Universitas Negeri Surabaya Tahun 2024 - Putri, Aura Marcenia; Fakhomah, Syafiyatul; Jamal, Adam (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2024)
This research aims to determine the decision-making styles and strategies used by HIMA 2024 leaders specifically in each study program within the FISIPOL scope. This research uses a qualitative method, namely research carried out by making participants as subjects which gives them the opportunity to answer the instruments given by the researcher. In this case, the researcher wants to obtain a subjective picture of the research participants by distributing a questionnaire. The author analyzed the research results based on the theory of Gelatt, Varenhorst and Carey (in Atwater, 1983) regarding decision making strategy and decision making style by Scott & Bruce (1995). The results of the research show that the majority of HIMA 2024 leaders within FISIPOL used the combination strategy in determining superior programs, namely 92.9% or 13 out of 14 respondents. The combination strategy is choosing an alternative by combining the highest possibility or opportunity with the desired result. Researchers also found that the majority of HIMA 2024 leaders within FISIPOL used a rational style in determining superior programs, namely 92.9% or 13 out of 14 respondents. The rational style is decision making using logic and mature details and is good at searching for information before making a decision.